FIX FREDDIE! – PULLING STRINGS TO REDUCE PRESSURE ON MINORS. Issue 9 (14th August 2014) - Cleugh, Francesca; Langseth, Annette; Clements, Charlotte; Salam, Menai; Manfredi, Lucia
Abstract : Objectives & Background: Emergency and urgent care workload is becoming unsustainable. 1 2 NW London has higher than average use of unscheduled care; 3 significant proportion with low acuity conditions. 2 4 5 As a paediatric emergency care provider, Imperial College Healthcare (ICHT) recognise a need to become proactive in tackling this challenge. ICHT collaborated with a professional puppet company to produce Fix Freddie! 6 A pilot tour ran in NW London March and April 2014. Objectives included: better understanding of how local community accesses unscheduled care gathering professionals across the whole system to support families in feeling confident to navigate system and care for their children's health needs reducing pressures on unscheduled care system Methods: Pilot tour explored different settings and workshop styles. Audience 484 children, 134 adults (image1 ) Parents and carers asked to complete pre show questionnaire about child health and services. After the show issues raised explored in various ways: small parent focus groups classroom-based discussion fete style event promoting conversations with professionals Feedback obtained with Post-It comments on "Freddie Feedback" poster (image 2). Filmed to capture impact of events on children, parents, professionals. Leaflet distributed with information about how to seek advice, self management and local services. Results:Pre show questionnaire: Completed by 46 parents of 85 children. 53% white british; 47% diverse ethnicies. Chart A -How they seek child health advice (image 3 ) Chart B -Services use when worried (image 3 ) Parents consistently worried by fever: 52% would seek GP review 41% would go to ED. Attended ED and the GP with similar illnesses. 26% reported issues in accessing care, primarily lack of same day GP appointments. Key themes surfaced from Fix Freddie! Feedback (image 4 ) Better understanding of local services, notably 111 Improved confidence managing minor ailments Positive feedback for puppet show and events Immediate impact captured on film, currently being analysed. Short documentary being produced by June 2014. Conclusion: Fix Freddie! has provided a fun and engaging way to make connections across the whole system, facilitating co-design of local solutions to problems of healthcare accessibility and confidence in self management. Local CCG commissioners are keen to fund a wider local tour and we are looking at next steps to broaden the reach of events.